2014
DOI: 10.1007/s10620-014-3088-4
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Intestinal Metaplasia and Tamoxifen: Can We Reverse the Inevitable?

Abstract: Gastric intestinal metaplasia can occur after chronic infection with Helicobacter pylori and is considered a precursor of gastric adenocarcinoma. Thus, interventions which can reverse intestinal metaplasia may reduce the incidence of gastric cancer. The manuscript by Moon et al. published in this issue of Digestive Diseases and Sciences [1] reports somewhat surprising results suggesting that Korean women receiving chronic tamoxifen treatment after breast cancer surgery showed a decrease in intestinal metaplasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“… 24 , 94 , 95 , 96 The ability to track these cell types in the preneoplastic state broadens options for more effective screening of subjects predisposed to eventually develop gastric cancer as well as to expand options for prophylactic therapy once atrophic gastritis develops, including antagonists of mTOR (mechanistic antagonist of rapamycin). 97 , 98 , 99 Although Hedgehog antagonists have been used for other cancer types, their use in clinical trials for gastric cancer is still in its infancy. 1 , 31 Where initiated, those trials have focused on targeting CD44-positive gastric stem cells to treat metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
“… 24 , 94 , 95 , 96 The ability to track these cell types in the preneoplastic state broadens options for more effective screening of subjects predisposed to eventually develop gastric cancer as well as to expand options for prophylactic therapy once atrophic gastritis develops, including antagonists of mTOR (mechanistic antagonist of rapamycin). 97 , 98 , 99 Although Hedgehog antagonists have been used for other cancer types, their use in clinical trials for gastric cancer is still in its infancy. 1 , 31 Where initiated, those trials have focused on targeting CD44-positive gastric stem cells to treat metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, prostaglandin E2 is believed to be involved in development of colon cancer, so it probably shouldn't be given to patients 37 . Nonetheless, these intriguing findings indicate that it may be possible to at least partially reverse atrophic gastritis 42, 44 . Evidence for a direct role of intestinal metaplasia or spasmolytic polypeptide-expressing metaplasia in gastric carcinogenesis is circumstantial; it is possible that reversal of atrophy may result in detectable changes (eg, related to transdifferention) that do not, however, significantly modify cancer risk 45 .…”
Section: Clinical Research Findingsmentioning
confidence: 98%
“…Because IM is a critical precursor in gastric carcinogenesis, the potential to reverse these lesions is of great interest. [ 5 ] Previous investigations have reported that eradication of H . pylori is sufficient to reverse IM, yet others have found that a significant proportion of patients still present with IM even after effective eradication.…”
Section: Introductionmentioning
confidence: 99%
“…pylori is sufficient to reverse IM, yet others have found that a significant proportion of patients still present with IM even after effective eradication. [ 5 ] IM is believed to be the ‘point of no return’ in the histological cascade from chronic gastritis to adenocarcinoma;[ 6 ] thus, efforts to understand the molecular mechanisms regulating the establishment and maintenance of IM are crucial to develop strategies to interrupt gastric carcinogenesis. For instance, CDX2 autoregulation is suggested to have a major impact on the stability of IM lesions.…”
Section: Introductionmentioning
confidence: 99%